The Contradiction of the Free Nutritious Eating Policy and the Reality of Honorary Teachers - Afrianus Friman; Rofinus Nenggor; Bedianus Namat (Journal of Political Innovation and Analysis, 2026)
Background: This article aims to examine the imbalance in priorities between one of the government’s flagship programs, the nutritious meals (MBG) program, and the reality of the welfare of honorary teachers in indonesia. On the one hand, the government allocates a significant budget to emphasize student nutrition in order to improve the quality of human resources towards the golden indonesia 2045.Objective: This study aims to analyze the contradictionbetween the policy of freenutritions meals for students and the reality of the welfare of honorary teachers, as well as assess its impact on the quality of education in indonesiaMethod: The research approach uses qualitative methods with literature studies, policy analysis, and in-depth interviews with honorary teachers in several school. Data was collected through official documents, news, and the direct experience of honorary teachers, then analyzed with thematic techhnigues to find patterns of contradictions and their implications.Findings and Implications: The MBG program benefits students in terms of nutritional intake but does not address the welfare problems of honorary teachers who continue to receive low salaries and lack social security protection. This policy imbalance has the potential to reduce the work motivation of honorary teachers and hamper education quality, as teachers experiencing economic hardship are unlikely to perform optimally.Conclusion: This study concludes that there is a real contradiction between the free nutritious food policy and the welfare conditions of honorary teachers.